Penerapan Aplikasi Android Pengenalan Huruf Hijaiyah Metode Waterfall Pada Paud Al Fina - Feri Prasetyo; Agus Dendi Rachmatsyah; Jumadi Nur; Faisal Adam (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
Recognition and mastery of the hijaiyah letters which are the basis for reading and studying the Holy Qur'an from an early age is very important, because if at the time of reading the hijaiyah letters you are accustomed to the wrong words it will cause different meanings so that we are required to read properly and correctly. The method in learning hijaiyah letters is usually given by traditional (conventional) reciting teachers or people often call it the sequential method. With this kind of teaching, children tend to be passive in accepting their teaching lessons, because the Koran teacher explains the children in learning to read hijaiyah letters orally, in writing and in body language. The application of recognizing hijaiyah letters is very effective and easy to use for students of paud al fina in recognizing and writing hijaiyah letters because the design of the learning aid program to read hijaiyah letters is a method in the form of visualization in the form of images, text and sound. To implement this method, the author uses Android Studio programming which acts as a tool (programming system) used to build an application, this application program is expected to generate interest for early childhood or adults who want to learn how to learn to read hijaiyah letters properly and correctly. accommodated.